Electrical charge transport and optical properties of iron pyrite - Shukla, Sudhanshu (Nanyang Technological University, 2017)
Iron pyrite is among the promising solar materials owing to its remarkably high optical absorption, optimal band gap, abundance, and non-toxicity. However, its solar conversion efficiency is limited to about 3 % mainly due to its low photovoltage. To address that, thin films prepared by spray pyrolysis, spin-coating of hot-injection synthesized nanocubes and pulsed laser deposition were sulfurized to obtain the pure pyrite phase. The film showed similar electrical properties and degenerate semiconducting behavior with Mott-VRH charge transport over a wide temperature range. Charge carrier dynamics in nanocube thin film revealed fast carrier localization and long-lived trap states in the pure pyrite. Temperature dependent electrical and magnetic behaviors supported the existence of intrinsic localized gap states. A non-standard, electrical experiment was carried out on a natural pyrite single crystal to assess the surface and bulk resistivities of pyrite which showed a significant difference in them for temperatures less than 120 K. It is concluded that the poor photovoltage generated by pyrite solar devices is due to the intrinsic defects in the material rather than to impurities or secondary phases.